In vitro induction of Entamoeba gingivalis cyst-like structures from trophozoites in response to antibiotic treatment - Becker, Christin; Adam, Aysegül; Dommisch, Henrik; Stach, Thomas; Schaefer, Arne S. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Entamoeba gingivalis (E. gingivalis) is an anaerobic protozoan that is strongly associated with inflamed periodontal pockets. It is able to invade the mucosal epithelium of the human host, where it can feed on epithelial cells and elicit a severe innate immune response. Unlike other Entamoeba species, it is considered that E. gingivalis cannot form cysts, because it is a non-infectious protozoan. The lack of encystation capability would make it susceptible to periodontal treatment. However, it is not clear how the human host becomes infected with E. gingivalis trophozoites. We investigated the ability of E. gingivalis to encapsulate in response to an unfavorable environment in vitro. Methods Different strains of E. gingivalis, isolated from inflamed periodontal pocket samples, were cultured for 8 days in the presence or absence of the antimicrobials amoxycillin and metronidazole. To reveal cyst formation, we investigated the morphology and ultrastructure of the amoeba by light, fluorescence, transmission and scanning electron microscopy. We also used the fluorescent dye calcofluor white M2R to demonstrate chitin present in the cyst wall. Results We observed exocysts and an intra-cystic space separating the encapsulated trophozoite from the environment. Remarkably, cysts showed a smooth surface, polygonal edges and smaller size compared to free-living trophozoites. In addition, encapsulated trophozoites that detached from the cyst wall had a dense cytoplasma without phagocytic vesicles. The cyst walls consisted of chitin as in other Entamoba species. The encapsulated trophozoids were mononuclear after antibioticinduced encapsulation. Discussion We conclude that E. gingivalis cyst formation has significant implications for dissemination and infection and may explain why established treatment approaches often fail to halt periodontal tissue destruction during periodontitis and peri-implantitis.